Effects of the 3D sizing of polyacrylonitrile fabric with carbon nanotube–SP1 protein complex on the interfacial properties of polyacrylonitrile/phenolic composites. (April 2016) - Abramovitch, Ido; Hoter, Nerya; Levy, Hagit; Gedanken, Aharon; Wolf, Amnon; Eitan, Asa; Fine, Tamir; Elmaleh, Lea; Shalev, Itzhak; Cohen, Galit; Grimberg, Elena; Nevo, Yuval; et al.
Polyacrylonitrile–phenolic composites display excellent in-plane properties but perform poorly when out-of-plane, through-thickness properties are considered. Composite architectures with carbon nanotubes, either dispersed within the matrix or bound to a fabric, in traditional composites have the potential to alleviate this weakness. However, effective reinforcement of composites using carbon nanotubes is difficult, due to poor dispersion and interfacial stress transfer and has thus far been met with limited success and at high costs. This paper describes an innovative and cost-effective technology to improve these inferior mechanical properties by using an exceptionally stable protein, SP1, for CNT attachment to PAN fabric, forming a three-dimensional nano-reinforced structure. This work confirms remarkable improvements in interlaminar shear strength and through-thickness tensile strength of SP1/CNT-reinforced polyacrylonitrile composites.